PENGUATAN APRESIASI BUDAYA DAERAH MELALUI PEMBELAJARAN BAHASA INGGRIS BERBASIS FLASHCARD WAYANG KULIT DI SLB BINA KARYA INSANI KARANGANYAR - Laksani, Hening; Pandanwangi, Brilindra; Pravitasari, Indriati Suci; Prilosadoso, Basnendar Herry; Iswara, Wildan Arya Praba; Itsar, Ahmad (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
Sekolah Luar Biasa (SLB) are formal educational institutions that play an important role in developing talents, abilities, and social lives for students with special needs, ensuring equal rights to education for all individuals. One of the methods that can support the success of the educational program is by using engaging interactive learning media. The media is beneficial for stimulating communication skills and potential optimally in order to support the achievement of learning objectives. The limited variety of learning media can hinder the learning process, especially in schools with special needs students who require assistance and attractive, enjoyable media. The solution to this problem is to provide learning media that not only emphasizes linguistic and communication aspects but also introduces the culture of the archipelago through visual media in the form of flashcards with wayang illustrations. The creation of these flashcards uses the design thinking method, which combines language knowledge through vocabulary, visual skills related to culture, and psychomotor competence in the learning process. It is hoped that these flashcard media can become an effective solution for children with special needs in learning activities, making the learning process more enjoyable and meaningful.